An assessment of the teaching and learning environment in Ghanaian Polytechnics under the Tertiary Education Reform Programme - Nutakor, Julius Enyo Kudjoe (2012)
A Thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the degree of Master of Science in Development Policy and Planning.